Alfred Russel Wallace na Amazônia: análise das descrições sobre a distribuição dos animais e seus limites de alcance - Soldado, Emerson Barão Rodrigues (2017)
Alfred Russel Wallace (1823-1913), English naturalist well-known for his studies on natural selection, chose Amazon as his first long range expedition. Between the years of 1848 to 1852, he observed and described the fauna, flora, geology and human groups that inhabited the surroundings. In these studies, Wallace also thoroughly addressed the subject of animal distribution, including figuring out the range limits of the species and their relations to the physical environment. Nevertheless, the maturation of these ideas as well as others just as important to the naturalist work only happened during a future expedition to the Malay Archipelago. An expedition of great notoriety that has become an object of analysis of many studies in present days. The present dissertation, however, specifically addresses the origins of ideas, such as the range limit of species, which remain linked to Wallace's Amazonian journey